2017
DOI: 10.1259/bjr.20160931
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radiation dose from abdominal quantitative CT with short scan length

Abstract: The dose to the patients from abdominal quantitative CT may be largely different from CTDI and SSDE. This study demonstrates the necessity of taking into account not only patient size but also scan length for evaluating the dose from short-length scans. Advances in knowledge: In CT examinations with 1-cm scan length, dose evaluation needs to take into account both patient size and scan length. An omission of either factor can result in an erroneous result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Despite the presence of a law regulating radiation protection and a national radiation protection agency in Cameroon 21 , the limitation of acquisition coverage remains uncertain in each hospital. The American Association of Physicists in Medicine (AAPM) Reports 111 and 204 have shown that the radiation dose from patient CT scanners depends on their size and length of scan 18 . Published studies have shown that reducing acquisition coverage 22 , 23 is a simple and effective way to limit the dose of patients and is recommended in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of a law regulating radiation protection and a national radiation protection agency in Cameroon 21 , the limitation of acquisition coverage remains uncertain in each hospital. The American Association of Physicists in Medicine (AAPM) Reports 111 and 204 have shown that the radiation dose from patient CT scanners depends on their size and length of scan 18 . Published studies have shown that reducing acquisition coverage 22 , 23 is a simple and effective way to limit the dose of patients and is recommended in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Radimetrics, researched and developed by Byer Healthcare from Germany, an analysis platform based on Monte-Carlo-Simulation was used to calculate the radiation doses of sensitive organs. 14,15 The total organ dose is calculated first for each slice using the CTDI vol at that slice and then summed over the slices that all into the scan region:…”
Section: Organ-specific-radiation Dose Levels Estimationmentioning
confidence: 99%